Biodiesel production from transesterification of Australian Brassica napus L. oil: optimisation and reaction kinetic model development - Hazrat M.A.; Rasul M.G.; Khan M.M.K.; Ashwath N.; Fattah I.M.R.; Ong H.C.; Mahlia T.M.I. (Springer Science and Business Media B.V., 2023)
Edible oil-based feedstocks based biodiesel is still leading the industry around the world. Canola oil (Brassica napus L.) contributes significantly to that race. Process optimisation and the development of reaction kinetic models of edible oil feedstocks are still required since the knowledge of kinetics is needed for designing industrial facilities and evaluating the performance of catalysts during transesterification or other related processes in a biorefinery. This research focuses on the transesterification process for biodiesel production because of its higher output efficiency, reactivity with feedstock, techno-economic feasibility in terms of FFA content, and environmental sustainability. The response surface method with the BoxBehnken model was used to optimise the process. Multivariate analysis of variance (ANOVA) was also performed to investigate the effectiveness of the regression model. The optimal process conditions were found to be 5.89M methanol, 0.5% (w/w) KOH, 60C and 120min. The predicted yield was 99.5% for a 95% confidence interval (99.1, 99.9). The experimental yield was 99.6% for these conditions. Two different kinetic models were also developed in this study. The activation energy was 16.9% higher for the pseudo-first-order irreversible reaction than for the pseudo-homogenous irreversible reaction. Such a comprehensive analysis will assist stakeholders in evaluating the technology for industrial development in biodiesel fuel commercialisation. 2022, The Author(s).